Capital defense : inside the lives of America's death penalty - Gould, Jon B.; Barak, Maya Pagni (New York Unviersity Press, 2019)
The unsung heroes who defend the accused from the ultimate punishmentWhat motivates someone to make a career out of defending some of the worst suspected killers of our time? In Capital Defense, Jon B. Gould and Maya Pagni Barak give us a glimpse into the lives of lawyers who choose to work in the darkest corner of our criminal justice system: death penalty cases. Based on in-depth personal interviews with a cross-section of the nation's top capital defense teams, the book explores the unusual few who voluntarily represent society's "worst of the worst."With a compassionate and careful eye, Gould and Barak chronicle the experiences of American lawyers, who--like soldiers or surgeons--operate under the highest of stakes, where verdicts have the power to either "take death off the table" or put clients on "the conveyor belt towards death." These lawyers are a rare breed in a field that is otherwise seen as dirty work and in a system that is overburdened, under-resourced, and overshadowed by social, cultural, and political pressures. Examining the ugliest side of our criminal justice system, Capital Defense offers an up-close perspective on the capital litigation process and its impact on the people who participate in it